Herramientas CAD/CAE en la caracterización tecnológica del Patrimonio Histórico Industrial: Aplicación a una prensa de aceite de oliva - José Ignacio Rojas Sola; Miguel Castro García; Mª del Pilar Carranza Cañadas; Francisco Javier Contreras Anguita (Virtual Archaeology Review)
The olive tree with its fruit, the olive, has been throughout history a culture whose importance has generated a widespread culture along the Mediterranean Sea. Since the days of ancient Egypt until today, its transformation to the consumption of olives, table olives or vegetable fat, has evolved hand in hand with contemporary techniques known. As for obtaining olive oil, fruit or the pressing of the pulp obtained after milling, is a critical point in its manufacture. This process is the goal of this communication which will present a technical analysis of an oil press. This is expected to achieve greater depth of knowledge of the techniques employed in the sector of olive oil.